Implicating the Role of GILZ in Glucocorticoid Modulation of T-Cell Activation - Cannarile, Lorenza; Delfino, Domenico V.; Adorisio, Sabrina; Riccardi, Carlo; Ayroldi, Emira (Frontiers in Immunology, 2019)
Glucocorticoid-induced leucine zipper (GILZ) is a protein with multiple biological roles that is upregulated by glucocorticoids (GCs) in both immune and non-immune cells. Importantly, GCs are immunosuppressive primarily due to their regulation of cell signaling pathways that are crucial for immune system activity. GILZ, which is transcriptionally induced by the glucocorticoid receptor (GR), mediates part of these immunosuppressive and anti-inflammatory effects, thereby controlling immune cell proliferation, survival, and differentiation. The primary immune cells targeted by the immunosuppressive activity of GCs are T cells. Importantly, the effects of GCs on T cells are partially mediated by GILZ. In fact, GILZ regulates T-cell activation and differentiation by binding and inhibiting factors essential for T-cell function. For example, GILZ associates with nuclear factor-κB (NF-κB), c-Fos, and c-Jun and inhibits NF-κB- and AP-1-dependent transcription. GILZ also binds Raf and Ras, inhibits activation of Ras/Raf downstream targets, including mitogen-activated protein kinase 1 (MAPK1), and inhibits forkhead box O3 (FoxO3) without physical interaction. GILZ also promotes the activity of regulatory T cells (Tregs) by activating transforming growth factor-β (TGF-β) signaling. Ultimately, these actions inhibit T-cell activation and modulate the differentiation of T helper (Th)-1, Th-2, Th-17 cells, thereby mediating the immunosuppressive effects of GCs on T cells. In this mini-review, we discuss how GILZ mediates GC activity on T cells, focusing mainly on the therapeutic potential of this protein as a more targeted anti-inflammatory/immunosuppressive GC therapy.